Hybrid Parenting - School Partnership in Islamic Education: Constructing Parents and Madrasah Relationships Based on an Islamic Digital Ecosystem - Sandi Ferdy Yulianto; Sukma Ayu Fadhila Ardianing; Muhamad Yasin (APPLICATION: Applied science in Learning Research, 2026)
The purpose of this study is to explore the collaboration pattern between parents and school within the Islamic digital ecosystem of MIN 1 Jombang amid the implementation of digitally based Islamic education. This research is grounded in the social constructivism perspective, which views educational relationships as socially constructed through interaction, communication, and the internalization of cultural and religious values in digital environments. This study employed a qualitative approach with an intrinsic case study design. Data were collected from March to May 2026 through unstructured interviews, participant observation, and documentation. Participants included madrasah administrators, teachers, parents, and students selected using purposive and snowball sampling techniques. Data analysis used the interactive model of Miles, Huberman, and Saldaña, consisting of data condensation, data display, and conclusion drawing and verification. The findings reveal that the digital Islamic ecosystem transformed parent–school relations from administrative communication into a collaborative and value-based educational partnership. Digital platforms function not only as communication media but also as socio-epistemic spaces for academic supervision, religious guidance, character building, and the internalization of Islamic values in students’ daily lives. The study identifies relational transformation, authority negotiation, collaborative monitoring, and value reproduction as key characteristics of the hybrid partnership model. Challenges include digital literacy gaps, communication overload among teachers, and blurred boundaries between professional and private spaces. This study contributes to the development of the Hybrid Parenting–School Partnership concept in digital Islamic education